Community Capacity Building and Sustainability: Outcomes of Community-Based Participatory Research - Hacker, Karen (2012)
BACKGROUND: For communities, the value of community-based participatory research (CBPR) is often manifested in the outcomes of increased capacity and sustainable adoption of evidence-based practices for social change. Educational opportunities that promote discourse between community and academic partners can help to advance CBPR and better define these outcomes. OBJECTIVES: This paper describes a community–academic conference to develop shared definitions of community capacity building and sustainability related to CBPR and to identify obstacles and facilitators to both. METHODS: “Taking It to the Curbside: Engaging Communities to Create Sustainable Change for Health” was planned by five Clinical Translational Science Institutes and four community organizations. After a keynote presentation, breakout groups of community and academic members met to define community capacity building and sustainability, and to identify facilitators and barriers to achieving both. Groups were facilitated by researcher–community partner teams and conversations were recorded and transcribed. Qualitative analysis for thematic content was conducted by a subset of the planning committee. RESULTS: Important findings included learning that (1) the concepts of capacity and sustainability were considered interconnected; (2) partnership was perceived as both a facilitator and an outcome of CBPR; (3) sustainability was linked to “transfer of knowledge” from one generation to another within a community; and (4) capacity and sustainability were enhanced when goals were shared and health outcomes were achieved. CONCLUSIONS: Community capacity building and sustainability are key outcomes of CBPR for communities. Co-learning opportunities that engage and mutually educate both community members and academics can be useful strategies for identifying meaningful strategies to achieve these outcomes.